Synergistic Interaction of Caspofungin Combined with Posaconazole against FKS Wild-Type and Mutant Candida auris Planktonic Cells and Biofilms - Noémi Balla; Fruzsina Kovács; Bence Balázs; Andrew M. Borman; Aliz Bozó; Ágnes Jakab; Zoltán Tóth; Ola Kobaissi; László Majoros; Renátó Kovács (MDPI AG, 2022)
Candida auris is a potential multidrug-resistant pathogen able to cause biofilm-associated outbreaks, where frequently indwelling devices are the source of infections. The number of effective therapies is limited; thus, new, even-combination-based strategies are needed. Therefore, the in vitro efficacy of caspofungin with posaconazole against FKS wild-type and mutant Candida auris isolates was determined. The interactions were assessed utilizing the fractional inhibitory concentration indices (FICIs), the Bliss model, and a LIVE/DEAD assay. Planktonic minimum inhibitory concentrations (pMICs) for the caspofungin-posaconazole combination showed a 4- to 256-fold and a 2- to 512-fold decrease compared to caspofungin and posaconazole alone, respectively. Sessile minimum inhibitory concentrations (sMICs) for caspofungin and posaconazole in combination showed an 8- to 128-fold and a 4- to 512-fold decrease, respectively. The combination showed synergy, especially against biofilms (FICIs were 0.033-0.375 and 0.091-0.5, and Bliss cumulative synergy volumes were 6.96 and 32.39 for echinocandin-susceptible and -resistant isolates, respectively). The caspofungin-exposed (4 mg/L) C. auris biofilms exhibited increased cell death in the presence of posaconazole (0.03 mg/L) compared to untreated, caspofungin-exposed and posaconazole-treated biofilms. Despite the favorable effect of caspofungin with posaconazole, in vivo studies are needed to confirm the therapeutic potential of this combination in C. auris-associated infections.